2018
DOI: 10.1007/s40091-018-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Single diagonal precast prestressed concrete bracing for strengthening existing concrete frames

Abstract: A new method for seismic retrofitting concrete structures is proposed using an X-shaped precast prestressed concrete brace. This PPC brace is made of four precast concrete parts and middle section that are assembled and added to the existing frame. This method has the following benefits: there is no need to work with wet concrete in site or anchor and bolt to the existing frame, which may lead to a fast and economic retrofitting method. The X-shaped concrete brace was made in half size and its efficiency is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In particular, it was confirmed that the seismic performance of existing R/C buildings with non-seismic characteristics can be efficiently improved through the seismic performance of the CCSS method and the established seismic strengthening design procedure. (7) In order to promote the commercialization of the technology, it is necessary to propose additional external joining methods that allow buildings to be used even during CCSS construction, and verification of different building topologies with different characteristics for different seismic hazard levels is required. Therefore, as a recommendation for future research, detailed and experimental research on the application of external joining and verification through nonlinear dynamic analysis is necessary.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was confirmed that the seismic performance of existing R/C buildings with non-seismic characteristics can be efficiently improved through the seismic performance of the CCSS method and the established seismic strengthening design procedure. (7) In order to promote the commercialization of the technology, it is necessary to propose additional external joining methods that allow buildings to be used even during CCSS construction, and verification of different building topologies with different characteristics for different seismic hazard levels is required. Therefore, as a recommendation for future research, detailed and experimental research on the application of external joining and verification through nonlinear dynamic analysis is necessary.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Meanwhile, representative seismic strengthening methods for existing R/C buildings without seismic reinforcement include strength reinforcement methods (the R/C wall installation method, section enlargement method, and steel brace method), deformation capacity improvement methods (the steel-plate reinforcement method, wire-mesh insertion reinforcement method, and fiber-reinforced polymer (FRP) reinforcement method), methods for improving the energy absorption capacity using seismic damping systems, and seismic isolation methods [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Typical seismic retrofitting methods for existing R/C buildings include using various reinforcing materials such as steel braces, precast concrete, and steel plates, as well as increasing the cross-sectional area through pouring. Representative types include the wall construction method, jacketing method, steel plate reinforcement method, and steel bracing seismic retrofitting [3][4][5][6][7][8][9][10][11][12][13]. However, all these seismic retrofitting methods have shortcomings [5,14,15], as listed below:…”
Section: Introductionmentioning
confidence: 99%